The study and constraints of breastfeeding mothers in performing endoprine massage and lactation in the working area of the Arjasa Health Center - Dewi Andariya Ningsih; Deni Maryani; Miftakhur Rohmah; Yuda Muhara Sari; Siti Romlah (Science Midwifery, 2022)
The lactation process can be problematic due to various factors. These factors can come from the mother, baby, management of breastfeeding and other factors. Factors from the mother can be caused by problems with the anatomy of the mother's breasts and nipples, conditions or diseases suffered by the mother. The failure of the lactation management process can also be caused by the mother's lack of exposure to information on how to breastfeed properly. This research is a quasi-experimental research. It took place from September to February 2022. This study involved 34 breastfeeding mothers and one of the active families, usually as decision makers in that family. This study uses a questionnaire. After that, the intervention of lactation massage and endoprin was given. This study used total sampling and using the McNemar TEST the results were 0.016 < 0.05, so it can be said that there were differences in lactation problems between before and after the intervention. The results of his research, the majority of family representatives strongly agree that they play a role in the success of breastfeeding mothers. In addition, they also need a face-to-face discussion group with health workers about breastfeeding. In carrying out its role as a mother, there are also two main obstacles faced by families in helping breastfeeding mothers, namely less breast milk and mothers who are shy about lactation massage and endhoprin. It is hoped that there will be further research related to how big the survey of the target community for lactation massage and endoprine